STUDY FISHING GROUND IN KAMPAR RIVER, MERANGIN VILLAGE, KUOK DISTRICT, PROVINCE OF RIAU - Tiur Anastasya Lestari Sitorus; Alit Hindri Yani; Nofrizal ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted in Mei 2015 in Kampar river, Merangin village,Kuok district, Province of Riau. Purpose of this study was to obtain data onenvironmental parameters become the benchmark fishing grounds and fishingactivity. Environmental parameters measured are temperature, current speed,brightness, depth, acidity (pH) and dissolved oxygen. After doing this research isthat the condition of the Kampar river Merangin village still quite good and stillsupport for life of organisms that were in it and deserves to fishing activities inthese waters.Keywords: fishing ground, environmental parameters, kampar kiri river